Marcel Mauss's economic vision, 1920–1925: Anthropology, politics, journalism. (February 2014) - Hart, Keith
Marcel Mauss took some time to resume his academic and political duties after the Great War, but the period 1920–1925 was one of intense activity and achievement on all fronts. He assumed Durkheim's responsibility as leader of a depleted Année Sociologique group and relaunched the journal. He was optimistic that his international socialist politics would bear national fruit and it did. He was also a prolific financial journalist at this time, writing about the exchange rate crisis of 1922–1924. He maintained a Chinese wall between these compartments of his life, briefly combining them in the last chapter of The Gift, which is only a tentative synthesis. This separation of his intellectual and political commitments makes it easier for anthropologists to ignore his politics and, worse, to perpetuate in his name that opposition between market contracts and gifts as economic principles that he wrote his famous essay to refute.